The fourth princess : a gothic novel of old Shanghai - Chang, Janie (William Morrow, an imprint of HarperCollins Publishers, 2026)
"Shanghai, 1911. Lisan Liu is elated when she is hired as secretary to wealthy American Caroline Stanton, the new mistress of Lennox Manor on the outskirts of Shanghai's International Settlement. However, the Manor has a dark past due to a previous owner's suicide, and soon Lisan's childhood nightmares resurface with more intensity andmeld with haunted visions of a woman in red. Adding to her unease is the young gardener, Yao, who both entices and disturbs her. Newly married Caroline looks forward to life in China with her husband, Thomas, away from the shadows of another earlier tragedy. But an unwelcome guest, Andrew Grey, attends her party and claims to know secrets she can't afford to have exposed. At the same party, the notorious princess Masako Kyo approaches Lisan with questions about the young woman's family that the orphaned Lisan can't answer. As Caroline struggles with Grey's extortion and Thomas's mysterious illness, Lisan's future is upended when she learns the truth about her past, and why her identity has been hidden all these years. All the while, strange incidents accelerate, driving Lisan to doubt her sanity as Lennox Manor seems unwilling to release her until she fulfills demands from beyond the grave." --